Lost in uncertainty: How the Euro crisis affected European identity constructions in national media discourses. (October 2019) - Lichtenstein, Dennis; Eilders, Christiane
The Euro crisis has revealed severe conflicts between EU member states and challenged a shared European identity. This article investigates how the crisis was reflected in identity constructions in media discourses in EU key countries. European identity construction is conceptualized as framing of the EU in favour or against belonging to the EU and togetherness with other members. Conducting a systematic content analysis of two weekly newspapers and magazines in Germany, France and the UK, we compare identity constructions between 2011 and 2014. Findings show that while support of belonging to the EU is low in general, the countries differ remarkably in terms of their sense of togetherness. This particularly applies to strong or weak political integration, market regulation or market freedom and financial stability or impulses for economic growth. The positions reflect long-term political conflicts between the countries but are also flexible enough to adapt to the particular event context.